Perlindungan Lingkungan Hidup sebagai Implementasi Asas Pembangunan Berkelanjutan dalam Perspektif Undang-Undang Nomor 32 Tahun 2009 - Dheri, Putriana Paulina (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze environmental protection as an implementation of the principle of sustainable development from the perspective of Law Number 32 of 2009 concerning Environmental Protection and Management, and to evaluate the effectiveness of the application of this principle in environmental policy and law enforcement in Indonesia. This study uses a normative legal method with a statutory and conceptual approach, through a review of norms in the 1945 Constitution of the Republic of Indonesia and the Environmental Management and Management Law, and is supported by secondary legal materials in the form of accredited journal articles for the 2021–2026 period and environmental law doctrine. The analysis is conducted descriptively-analytical and prescriptively using systematic and teleological interpretations to assess the suitability of legal norms, principles, and instruments with development implementation practices. The results of the study indicate that normatively the Environmental Management and Management Law has internalized the principle of sustainable development through the regulation of preventive instruments (KLHS and AMDAL), environmental licensing mechanisms, and a comprehensive administrative, civil, and criminal law enforcement system. However, the effectiveness of its implementation still faces structural and cultural obstacles, particularly in consistent oversight and law enforcement. Therefore, institutional strengthening, apparatus integrity, and optimization of public participation are needed to achieve substantive sustainable development.